Why Does Classroom‐Level Victimization Moderate the Association Between Victimization and Depressive Symptoms? The "Healthy Context Paradox" and Two Explanations. Issue 5 (1st July 2021) - Pan, Bin; Li, Tengfei; Ji, Linqin; Malamut, Sarah; Zhang, Wenxin; Salmivalli, Christina
Abstract : The present longitudinal study examined how and why classroom‐level victimization moderates the prospective association between peer victimization and depressive symptoms with 2, 643 third‐ and fourth‐graders ( M age  = 10.01 years) in China. Multilevel modeling revealed that peer victimization was more strongly associated with increasing depressive symptoms in classrooms with lower classroom‐level victimization. Moreover, two mechanisms were identified to explain the moderating effect of classroom‐level victimization. First, low classroom‐level victimization reduced victimized children's received friendship nominations from peers, thereby leading to increases in depressive affect. Second, low classroom‐level victimization affected victimized children's depressive symptoms through damage to their social self‐concept. These findings provide support for the "healthy context paradox" in the Chinese culture, and highlight the mechanisms of this phenomenon.